Amazonian Kichwa of the Curaray River : Kinship and History in the Western Amazon - Reeve, Mary-Elizabeth (Book collections on Project MUSE., 2022)
This ethnography explores ways in which Amazonian Kichwa narrative, ritual, and concepts of place link extended kin groups into a regional society within Amazonian Ecuador.